2019
DOI: 10.3389/fnut.2019.00022
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Counseling for Head and Neck Cancer Patients Undergoing (Chemo) Radiotherapy—A Prospective Randomized Trial

Abstract: Background: Locally advanced head and neck cancer is managed either by combined surgery and (chemo) radiotherapy or definitive (chemo) radiotherapy, which may deteriorate nutritional status. Previous data have shown that intensive nutritional intervention by a dietician reduces radiation-induced adverse events including weight loss.Objective: To determine if on-demand nutritional counseling (ODC, control group) would be as efficacious as intensive nutritional counseling (INC, experimental group) in patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(99 citation statements)
references
References 40 publications
(63 reference statements)
2
80
0
17
Order By: Relevance
“…Similar to other studies [15,16,19], we observed that those who used ONS showed less weight loss (except of the overweight) and consumed more protein (0.14 g/kg/day). Additionally, malnourished patients lost less weight, while overweight patients lost more weight, showing that the initial BMI defines the BWC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to other studies [15,16,19], we observed that those who used ONS showed less weight loss (except of the overweight) and consumed more protein (0.14 g/kg/day). Additionally, malnourished patients lost less weight, while overweight patients lost more weight, showing that the initial BMI defines the BWC.…”
Section: Discussionsupporting
confidence: 90%
“…An additional finding was an accumulated deficit of weight loss that was found before the start of treatment. Corroborating these findings, Orell et al [16] found that overweight patients lost more weight due to symptoms such as anorexia and nausea. According to the Aspen Guideline [48], critically ill patients with obesity have greater complications when compared to patients with normal weight classified by BMI and have an indication for assessment and early nutritional support.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The guidelines framed by expert committees stress on the core treatment modalities. But the importance of keeping the supportive care ongoing in the form of nutritional support which is an integral part of cancer care and is particularly of importance for patients with head and neck cancers and gastrointestinal tract cancers, 20,21 psychological and peer group support 22 have not found importance. The strategies adopted by the organizations providing cancer care also did not spell out clearly their standpoint to keep these services running.…”
Section: Discussionmentioning
confidence: 99%
“…In the evaluation of muscle strength in patients with cancer, hand grip strength measurement has been widely used as a standard approach [30]. Previous studies showed that reduced hand grip strength is associated with worse prognosis [31,32] and poor treatment outcome [33,34]. However, these studies involved patients with cancer with a longer prognosis who are receiving anticancer treatment.…”
Section: Discussionmentioning
confidence: 99%